Deplete and repeat: microglial CSF1R inhibition and traumatic brain injury - Boland, Rebecca; Kokiko-Cochran, Olga N. (Frontiers in Cellular Neuroscience, 2024)
Traumatic brain injury (TBI) is a public health burden affecting millions of people. Sustained neuroinflammation after TBI is often associated with poor outcome. As a result, increased attention has been placed on the role of immune cells in post-injury recovery. Microglia are highly dynamic after TBI and play a key role in the post-injury neuroinflammatory response. Therefore, microglia represent a malleable post-injury target that could substantially influence long-term outcome after TBI. This review highlights the cell specific role of microglia in TBI pathophysiology. Microglia have been manipulated via genetic deletion, drug inhibition, and pharmacological depletion in various pre-clinical TBI models. Notably, colony stimulating factor 1 (CSF1) and its receptor (CSF1R) have gained much traction in recent years as a pharmacological target on microglia. CSF1R is a transmembrane tyrosine kinase receptor that is essential for microglia proliferation, differentiation, and survival. Small molecule inhibitors targeting CSF1R result in a swift and effective depletion of microglia in rodents. Moreover, discontinuation of the inhibitors is sufficient for microglia repopulation. Attention is placed on summarizing studies that incorporate CSF1R inhibition of microglia. Indeed, microglia depletion affects multiple aspects of TBI pathophysiology, including neuroinflammation, oxidative stress, and functional recovery with measurable influence on astrocytes, peripheral immune cells, and neurons. Taken together, the data highlight an important role for microglia in sustaining neuroinflammation and increasing risk of oxidative stress, which lends to neuronal damage and behavioral deficits chronically after TBI. Ultimately, the insights gained from CSF1R depletion of microglia are critical for understanding the temporospatial role that microglia develop in mediating TBI pathophysiology and recovery.Author Contributions RB wrote the paper. OK-C provided expertise and edited the paper. Both authors contributed to the article and approved the submitted version.